2022
DOI: 10.3389/fevo.2022.939374
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Palaeoenvironmental Record to Better Understand Long-Term Human-Environment Interaction in Inner Asia During the Late Holocene

Abstract: The Middle to Late Holocene spread of agropastoralism throughout Eurasia not only subjected domesticated taxa to stressors associated with novel environments but also induced changes in these environments following the introduction of these social-ecological systems. The mountainous region of Inner Asia comprises various steppe, meadow, and forest landscapes where zooarchaeological evidence suggests occupation by herding populations as early as 7,000 years Before Present (BP). Recent archaeobotanical findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…Paleoclimatic data from this part of the Tien Shan mountains show an increase in moisture at the onset of agricultural dispersal around 4000 BCE (Chen et al, 2016). Within the humid episodes that likely facilitated agriculture dispersal in the mountain highlands, several rapid cold episodes were detected at around ∼2200 BCE and ∼700 BCE (Leroy and Giralt, 2021;Spate et al, 2022). The identified cooling episodes roughly overlap with the abandonment of the Chap II and Chap I sites (Figure 9).…”
Section: Discussionmentioning
confidence: 90%
“…Paleoclimatic data from this part of the Tien Shan mountains show an increase in moisture at the onset of agricultural dispersal around 4000 BCE (Chen et al, 2016). Within the humid episodes that likely facilitated agriculture dispersal in the mountain highlands, several rapid cold episodes were detected at around ∼2200 BCE and ∼700 BCE (Leroy and Giralt, 2021;Spate et al, 2022). The identified cooling episodes roughly overlap with the abandonment of the Chap II and Chap I sites (Figure 9).…”
Section: Discussionmentioning
confidence: 90%
“…Presently there is no evidence for irrigation infrastructure at the site, although this interpretation is limited by the lack of broader spatial data outside the excavated sounding. Given the relatively wetter environmental conditions (Ran and Feng, 2013; Spate et al, 2022; Tarasov et al, 1997) in Westerly dominated areas north of the Tien Shan during the Late-Holocene period around 3000 BP there may have been sufficient water availability for irrigated rice cultivation in the foothill regions below Luanzagangzi. This region has also had growing degree days (GDDs) above 3000 (Zhang et al, 2022) through the Late-Holocene, meeting another requirement of rice cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Li (2021) defines the 'intensification' of agriculture post-3300 BP as a greater involvement in and reliance on cultivation and irrigation, evidenced by the further spread of archaeobotanical materials, the proliferation of farming and cereal processing tools, and isotopic evidence for irrigation of plants or increased millet consumption by humans or animals. A palaeoenvironmental review (Spate et al, 2022) also identifies a number of perturbations in three northern Xinjiang records that may be associated with more intensive agricultural land use through this period.…”
Section: Late-holocene Agriculture and Environment In Northern Xinjiangmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in speleothem and tree-ring studies over recent years has revealed new insights into the climate in order to interpret the region's historical human-environment interactions [10,11]. An increasing number of local paleoenvironmental reconstructions are becoming available to enable the better understanding of historical human activity patterns [12][13][14]. Archaeological and historical research has established a framework for the history of human activity in the Tarim Basin.…”
Section: Introductionmentioning
confidence: 99%